Employment, flexible working and the family - Crompton, Rosemary (The British Journal of Sociology, 2002)
This paper assesses some of the implications of one of the major social changes to have taken place in the West during the second half of the twentieth century — that is, the increased employment of women, together with normative changes in gender relations and in women's expectations. These changes have been linked to an increase in individualism, which itself is associated with the transcendence of ‘first modernity’. Thus it is suggested that new approaches to social analysis are required (Beck). Here it is argued that, rather than develop completely new approaches in order to grasp the changes that are under way, the ‘economic’ and the ‘social’ (that is, employment and the family) should be seen as intertwined, rather than approached as separate phenomena. Past debates in feminism, changes in the family, and flexible employment are critically examined. The growing tensions between employment and family life are discussed. It is argued that these changes are associated with the intensification of capitalist development, rather than reflecting a fundamental transformation of society. Existing approaches to the analysis of social change, including Polanyi's analysis of the development of ‘counter-movements’ against the ‘self-regulating’ market, will, therefore, still be relevant to our enquiries. In the concluding section, a programme of research that would examine these changes is outlined.
Keywords: capitalism; family; flexible employment; gender; modernity

Anomie, Social Change and Crime - Bernburg, Jon Gunnar (British Journal of Criminology, 2002)
The last decade has seen a revived interest in using anomie theory in crime and deviance research. The present paper contributes to this development by offering an examination of a particular extension of anomie theory, namely, Messner and Rosenfeld's Institutional-Anomie theory. Explicating Institutional-Anomie theory relative to the sociologies of Durkheim, Merton and Polanyi, I find that this theory goes beyond Merton by using a strain of thought that is critical of liberal society. By bringing in the notion of the disembedded market economy, a central notion in the institutionalism of Polanyi and Durkheim, this theory links crime, anomie, and contemporary social change. I also discuss some of the limitations of linking crime with societal level processes in a Durkheimian rather than Mertonian manner.
Keywords: DURKHEIM, Emile; MERTON, Robert; anomie; crime; criminology; disembeddedness

The 'new contractualism', social protection and the Yeatman thesis - Gaby Ramia (Journal of Sociology, 2002)
An important characteristic of public policy formulation over the 1980s and 1990s, particularly in the English-speaking countries, has been the increasing use of contractual principles as regulatory tools. The 'new contractualism' represents the recent re-emergence and adaptation of the social contract of the 17th and 18th centuries and the classical legal contract that emerged in the 19th century. The work of Anna Yeatman provides the most cogent and influential, non-neo-liberal scholarly appraisal of the new contractualism. Yeatman argues that the current contractualist agenda is consistent with equality of opportunity, occasioning a redefinition of citizenship so as to improve on the discourse of social protection. This paper argues that any attempt to remove social protection flawed though it is from discussions of the new contractualism is artificial. The social justice implications of such a position are perilous, for policy formulation has not yet entered a phase in which social protection can be superseded in a way which does not violate the rights of the socio-economically disadvantaged.
Keywords: English-speaking countries; YEATMAN, Anna; citizenship; commodity fiction; contractualism; double movement; equality; fictitious commodities; governance; human rights; political planning; social justice; social movements; social protection; sociology

Towards a Theory of Values-Based Labeling - Barham, Elizabeth (Agriculture and Human Values, 2002)
An outline of a theory of values-based labeling as a social movement argues that it is motivated by the need to re-embed the agro-food economy in the larger social economy. A review of some basic premises of embeddedness theories derived from the work of Karl Polanyi reveals their connection to particular values-based labeling efforts. From this perspective, values-based labeling presents itself as primarily an ethical and moral effort to counter unsustainable trends within presently existing capitalism. These labels distinguish themselves from ordinary commercial labels by a focus on process and on quality. Evaluating the transformative potential and progressive nature of values-based labeling poses a key challenge. One avenue for gauging this potential is conventions theory. This approach can be adapted to consider the decision making processes that go on within values-based labeling groups, as well as consumer decision making based on such labels, as instances of what is termed a politics of ethical judgment. The conclusion emphasizes the need for more research in this area and suggests how it could be furthered.
Keywords: agricultural policy; agro-food economy; embeddedness; food policy; household production and intrahousehold allocation; marketing; relation of economics to social values; social economy

Proximité spatiale et relations science - industrie : savoirs tacites ou encastrement (Polanyi ou Polanyi) ?, Spatial proximity and relations between academic research and firms : tacit knowledge or embeddedness (Polanyi or Polanyi) ? - Grossetti, Michel; Bès, Marie-Pierre (Revue d’Économie Régionale & Urbaine, 2002)
RésuméLes notions d’encastrement et de savoirs tacites sont souvent utilisées dans des théories expliquant les effets de proximité spatiale dans les relations entre la recherche académique et les entreprises. Même si elles ont des origines proches (ne serait-ce que parce qu’elles ont été formulées à l’origine par deux frères, Karl et Michael POLANYI), elles ont des implications très différentes en ce qui concerne l’interprétation des effets de proximité. Dans un cas (l’encastrement), on peut généraliser l’explication aux effets de proximité dans les relations entre organisations alors que dans l’autre cas (savoirs tacites), l’explication se restreint aux échanges en matière de connaissance. L’analyse d’un corpus de cas de collaboration entre les laboratoires du CNRS et les entreprises plaide en faveur de la thèse de l’encastrement., ENG: The notions of embeddedness and tacit knowledge are often used in the theories explaining spatial proximity effects in the relations between academic research and firms. Even if the two notions have a close origin (they have been defined by two brothers, Karl and Michael POLANYI), they imply different views on spatial proximity effects. In one case (embeddedness), it is possible to generalize the explanation of spatial proximity effects to all kinds of relations between organizations. In the other case (tacit knowledge), only knowledge spillovers can be explained. The analysis of a set of cooperations between firms and french academic laboratories suggests that embeddedness thesis is better.Classification JEL : O18.
Keywords: POLANYI, Michael, 1891-1976; embeddedness; encastrement; proximité; savoirs tacites; science-industrie; tacit knowledge

Globalization and Democracy: A New 'Great Transformation'? - Munck, Ronaldo (Annals of the American Academy of Political & Social Science, 2002)
Examines the relationship between democracy and development to set the scene for the pressing contemporary issue of how globalization might affect democracy and vice versa. Reference to the work of Karl Polanyi who posited a dual movement of market expansion matched by increasing social control over it; Impact of globalization.
Keywords: POLANYI, Karl, 1886-1964; democracy; double movement; economic development; globalization

The Great Depression and the Decline of Liberal Capitalism: Polanyi and Schumpeter - Trigilia, Carlo (Economic Sociology, 2002)
This chapter contains section titled: * Market Domination and Society's Self-Defense * The Decline of the Bourgeoisie and Anti-Capitalist Policies * Analytical Convergence and Political Divergence
Keywords: SCHUMPETER, Joseph Alois, 1883-1950; capitalism; depression; economic level; economic sociology; international relations; social conditions